2013
DOI: 10.1371/journal.pone.0055732
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Cucurbitacin B in BRCA1 Defective Breast Cancer Cells

Abstract: Cucurbitacin B (CuB) is one of the potential agents for long term anticancer chemoprevention. Cumulative evidences has shown that cucurbitacin B provides potent cellular biological activities such as hepatoprotective, anti-inflammatory and antimicrobial effects, but the precise mechanism of this agent is not clearly understood. We examine the biological effects on cancer cells of cucurbitacin B extracted from a Thai herb, Trichosanthes cucumerina L. The wild type (wt) BRCA1, mutant BRCA1, BRCA1 knocked-down an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 53 publications
0
16
1
Order By: Relevance
“…This study showed an IC50 of 8μM in MDA-MB-231 cells after 48h of treatment. On the other hand, Promkan et al observed an IC50 of 70μM (38.9μg/ml) after 48h of treatment [44]. In contrast to these studies, our study showed significantly reduced effective concentrations of CuB.…”
Section: Discussioncontrasting
confidence: 99%
“…This study showed an IC50 of 8μM in MDA-MB-231 cells after 48h of treatment. On the other hand, Promkan et al observed an IC50 of 70μM (38.9μg/ml) after 48h of treatment [44]. In contrast to these studies, our study showed significantly reduced effective concentrations of CuB.…”
Section: Discussioncontrasting
confidence: 99%
“…The gherkin is also used for traditional medicinal purpose such as stomach ache, jaundice, hemorrhoids and preventing stone formation in kidney (Jeyakumar et al, 2014). It was previously reported that there are many useful phytochemical constituents from gherkin, for example cucurbitacin B, cucurbitacin D and cucurbitacin G. Cucurbitacin B have potential to be used as a favorable phytochemical for cancer prevention (Promkan et al, 2013). Gherkin plant and vegetable contains of many potential compounds such as phenolics, flavonoids, tannins, alkaloids, saponins and steroids which contained high level of antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…Cucurbitacin B (CuB) is one of the most abundant forms of cucurbitacins and the most widely used as an anticancer agent. It has significant anti-inflammatory activity and is used traditionally to treat hepatitis (9). Studies indicate that CuB is capable of inhibiting the growth of a wide spectrum of malignant human cells, including myeloid leukemia, breast cancer, glioblastoma multiforme, pancreatic cancer, laryngeal cancer, melanoma and osteosarcoma cells (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%